2004
DOI: 10.1021/ic048939z
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Metalloprotein Folding Using a de Novo Design Strategy

Abstract: Metal ions play significant roles in most biological systems. Over the past two decades, there has been significant interest in the redesign of existing metal binding sites in proteins/peptides and the introduction of metals into folded proteins/peptides. Recent research has focused on the effects of metal binding on the overall secondary and tertiary conformations of unstructured peptides/proteins. In this context, de novo design of metallopeptides has become a valuable approach for studying the consequence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
111
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
3

Relationship

6
4

Authors

Journals

citations
Cited by 87 publications
(113 citation statements)
references
References 133 publications
2
111
0
Order By: Relevance
“…The heptad is composed of seven amino acid residues, denoted as abcdefg , where a and d positions are usually hydrophobic residues, and e and g positions are salt-bridging residues. 704,705 The connectivities between helices and overlapping hydrophobes are often represented as helical wheel diagrams (Figure 29). For heptads containing leucine, the addition of each 7 amino acid repeat confers ~9 kcal/mol of stability to the system.…”
Section: De Novo Designmentioning
confidence: 99%
“…The heptad is composed of seven amino acid residues, denoted as abcdefg , where a and d positions are usually hydrophobic residues, and e and g positions are salt-bridging residues. 704,705 The connectivities between helices and overlapping hydrophobes are often represented as helical wheel diagrams (Figure 29). For heptads containing leucine, the addition of each 7 amino acid repeat confers ~9 kcal/mol of stability to the system.…”
Section: De Novo Designmentioning
confidence: 99%
“…[19] These studies demonstrated that modification of steric bulk around the metal-binding site could control solvent/substrate access to the metal. The first generation CuNiR model peptide, TRI W-H, contains a Leu residue at the d -sites [20] above and below the Cu-binding histidines in the 23 rd position, in a fashion analogous to TRIL16C. Therefore, we substituted the Leu residues at the 19 th and 26 th positions in three different ways.…”
mentioning
confidence: 99%
“…[4] In particular, we have asked whether the same metal can be bound to structurally related peptides with identical first-coordinationsphere ligands derived from the protein, but in one case form a trigonal structure and in a second case form a fourcoordinate pseudo-tetrahedral environment. [4] The relative importance of a metals geometric preference and the inherent protein structure is fundamental to understanding the folding, [5][6][7][8] stability, [9,10] and conformational changes [4,5,11] of metalloproteins, and hence the control of such site discrimination has been an important objective of protein design studies. The peptides described herein are variants of the TRI family of peptides shown in Table 1.…”
mentioning
confidence: 99%